The Crucial Role of Social Workers in Supporting Students' Well-Being and Education - Mamuaya, Chriestine Lucia (Universitas Tanjungpura, 2025)
School social workers in Indonesia play a pivotal role in improving students’ emotional, mental, and social well-being. This literature review identifies four major functions: (1) providing counseling and mental health support that enhance academic engagement and resilience; (2) advocating for disadvantaged students by facilitating access to aid programs such as PKH and KIP; (3) collaborating with teachers to implement early detection and anti-bullying programs that reduce behavioral problems; and (4) assisting students from low-income families in accessing social welfare services to prevent school dropout. The review reveals that schools with active social work programs report fewer disciplinary cases and higher learning motivation. However, critical barriers persist, including a severe shortage of trained personnel, unequal access to mental health services in rural areas, and limited institutional recognition of social workers’ professional roles. These findings highlight the urgent need for policy reform, expansion of the social work workforce, and stronger intersectoral collaboration. Strengthening these aspects will help create an equitable and supportive school environment that fosters both academic success and holistic student well-being.